Reduction of incompatible intermixing of different steel grades in continuous casting by optimizing the casting sequence. (4th May 2022) - Ramstorfer, Franz; Delane de Souza, Marco
ABSTRACT: The demand for long casting sequences together with a wide range of different steel grades inherently leads to the generation of incompatible steel intermixing during a grade change. This paper describes the development of an optimisation tool for casting sequences based on a mixing model. The mixing model accounts for mixing in the tundish and in the liquid core of the strand and was calibrated based on samples of the chemical composition taken from slabs containing intermixed steel. The optimisation of the casting sequence order by minimising incompatible intermixing was accomplished by applying heuristic optimisation algorithms developed for the solution of the 'Traveling Salesman Problem'.